Fatty Acid Profiles and Cholesterol Composition of Venison from Farmed Deer - Ismail, Dahlan; Azmi, Norfarizan Hanoon Noor (Medwell Publishing, 2007)
It is important to evaluate venison characteristics as a new high quality red meat in the meat marketing system. This information is vital to ensure their commercial success and dietary benefits. The aim of this study is to determine the venison quality from farmed deer according to cuts or muscles based on fatty acid profiles and cholesterol content and to do comparative study on venison quality between species of farmed deer (rusa, sarnbar, fallow and imported red deer) and feeding regimens, i.e., grass-fed vs concentrate-fed venison. The samples of venison were derived from javan rusa (Cervus timorensis russa), moluccan rusa (Cervus timorensis moluccensis), sarnbar (Cervus unicolor brookei), fallow (Dama dama) and imported red deer (Cervus elaphus). Moluccan rusa and red deer were grass-fed deer. Javan rusa, sambar and fallow deer were concentrate-fed deer. Cholesterol content in Longissimus Dorsi (LD) muscles of sambar, fallow and rusa deer were 75.36, 76.61 and 77.58 mg l00g- 1 of fresh venison, respectively. Cholesterol content in Biceps Femoris (BF) muscles of moluccan rusa, sambar, fallow and red deer were 56.61, 59.26, 86.37 and 98.44 mg 100g-1 of fresh venison, respectively. Concentrate-fed deer LD and Psoas Major (PM) muscles show higher C18:2 (n-6) than grass-fed deer. Grass-fed rusa deer shows the highest C18:3 (n- 3) percentages in PM muscle. Grass-fed rusa and red deer gave an ideal n-6:n-3 ratio of less than 5. Species of deer did not influence n-6:n-3 ratio and fatty acid composition in venison. Feeding regimens (grass-fed vs concentrate-fed) significantly (p<O.05) influence n-6:n-3 ratio, fatty acid profiles and cholesterol content in the venison of farmed deer in this study.